Socio-Cultural Aspects of Diabetic Foot: An Ethnographic Study and an Integrated Model Proposal - Davide Costa; Giuseppe Gallelli; Enrica Scalise; Nicola Ielapi; Umberto Marcello Bracale; Raffaele Serra (Societies)
Background: Diabetes mellitus (DM) is an ongoing and growing health problem worldwide, with a series of important complications such as diabetic foot that can significatively reduce the quality of life of affected patients. This study aims to explore the socio-cultural aspects of patients with diabetic foot, analyzing the following research question: “What are the socio-cultural aspects experienced by patients with diabetic foot?” Methods: A qualitative design using an ethnographic approach was applied to study the social and cultural aspects of Italian diabetic foot patients. Results: We included 20 key informants: 13 men and 7 women. Ages ranged from 54 to 71, with an average age of 61.2. The data analysis revealed five main themes: perceptions of diabetic foot, living with diabetic foot, impacts of culture and economic performance, barriers to health and diabetic foot, and home remedies and alternative medicine. Conclusions: This study provides a new perspective on the influence of cultural factors on the health of diabetic foot patients, showing various factors related to a lack of knowledge and training, fear, and acceptance of diabetic foot. This study also presents a new integrated model which will allow patients and practitioners to act on the various critical issues that emerged from our research.